2021
DOI: 10.1177/10105395211014647
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Regarding Coronavirus Disease Among Patients Visiting Eye Hospitals of Province Number 2, Nepal

Abstract: The present study aims to explore knowledge, attitudes, and practices regarding COVID-19 and level of satisfaction with efforts to halt the further spread of the disease among patients visiting eye hospitals in province number 2, Nepal. All eligible patients (n = 1112) presenting during the study period were interviewed using a validated semistructured questionnaire. The level of awareness was significantly associated with educational attainment and district of residence. Different myths and misconceptions reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…The respondents having white-collar occupations mostly have easy access to information, and strong learning ability further aids in increasing their attitude and practice. Our study further revealed that the highly educated respondents had good KAP on COVID-19, and this bears a resemblance to the study conducted in North East Ethiopia [39], North West Ethiopia [40], Nepal [56], Iran [48], Pakistan [52] and Bangladesh [41,42]. Highly educated people are more sensitive and better understand pertinent issues in society.…”
Section: Plos Global Public Healthsupporting
confidence: 80%
See 1 more Smart Citation
“…The respondents having white-collar occupations mostly have easy access to information, and strong learning ability further aids in increasing their attitude and practice. Our study further revealed that the highly educated respondents had good KAP on COVID-19, and this bears a resemblance to the study conducted in North East Ethiopia [39], North West Ethiopia [40], Nepal [56], Iran [48], Pakistan [52] and Bangladesh [41,42]. Highly educated people are more sensitive and better understand pertinent issues in society.…”
Section: Plos Global Public Healthsupporting
confidence: 80%
“…In addition, previous studies conducted on Ethiopia [38][39][40], Bangladesh [41,42], Turkey [43], China [44][45][46], Malaysia [47], Iran [48], Indonesia [49], and Cameroon [50], Uganda [51], Pakistan [52], Bhutan [53] regarding knowledge, attitudes and practices (KAP) on COVID-19 also provided substantiation of clear understanding of these concerns further underscored the significance of the study. Some studies were conducted about KAP on COVID-19 in the context of Nepal as well [54][55][56][57][58][59][60]. However, the uniqueness of our study is it was focused on most affected districts of Nepal with a higher number of cases.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in knowledge was guided by the level of education with exceptions being between people who had basic education and secondary level education, and between people with a masters and above and bachelors. 11,21,22 Education levels also significantly affected attitudes with people with no formal education showing more negative attitude than the other groups. Nevertheless, practice regarding COVID was not seen to be affected by the level of education in this study.…”
Section: Discussionmentioning
confidence: 99%